Kin recognition by odor discrimination in dwarf hamsters (Phodopus campbelli) using an habituation paradigm - Godin, Jessica Maie (Kansas State University, 2007)
Male and female Phodopus campbelli were investigated for kin recognition abilities, assessed by kin discrimination of bedding, urine, fecal, or midventral glandular secretion odors. Using a habituation-discrimination paradigm, subjects were presented either the odors of a pair of their own brothers (C[subscript 1]) or a pair of brothers that were unrelated to them (C[subscript 2]). All subjects were then presented with a final test discrimination odor from a male donor unrelated to themselves or the first donors. All subjects differentiated between the bedding and glandular odors of two unrelated males, regardless of condition assignment. Subjects did not statistically differentiate between the odors of two brothers. These results suggest Phodopus campbelli are capable of recognizing kin based on bedding and midventral gland odors.
Keywords: Dwarf hamster; Kin recognition; Kin discrimination; Odor discrimination; Habituation-discrimination; Biology, Ecology (0329); Psychology, Behavioral (0384); Psychology, Experimental (0623)